The return of borders in the world economy: An EU-perspective - Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2023)
This paper examines the European Union's changing perspective on globalization, reflecting a shift from its traditionally open, rules-based trade policy. The rise of internal protectionist measures, coupled with increasing economic insularity in the US and China, are challenging this policy. The study advocates revitalizing the EU's internal market and fostering robust international trade policies, contrasting this with the current trend of implementing various types of selective industry support. It further underscores the EU's heightened responsibility in global trade liberalization, emphasizing the urgency for new trade agreements, particularly with the US, and a reinvigorated role for the WTO.
Keywords: F02; F15; F51; 330; Globalization; European Union; Protectionism; Industrial Policy